2017
DOI: 10.1177/1527154417728514
|View full text |Cite
|
Sign up to set email alerts
|

Political Efficacy and Participation of Nurse Practitioners

Abstract: Twenty-eight states have laws and regulations limiting the ability of nurse practitioners (NPs) to practice to the full extent of their education and training, thereby preventing patients from fully accessing NP services. Revisions to state laws and regulations require NPs to engage in the political process. Understanding the political engagement of NPs may facilitate the efforts of nurse leaders and nursing organizations to promote change in state rules and regulations. The purpose of this study was to descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 28 publications
4
23
1
Order By: Relevance
“…While internal political efficacy is defined as the confidence in one's own capabilities to understand and impact the politics, external political efficacy is defined as the confidence that the political system should be responsive to individual needs (Levy, ). Having a sense of being able to affect the political process is strongly correlated with political participation (O'Rourke, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While internal political efficacy is defined as the confidence in one's own capabilities to understand and impact the politics, external political efficacy is defined as the confidence that the political system should be responsive to individual needs (Levy, ). Having a sense of being able to affect the political process is strongly correlated with political participation (O'Rourke, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the size of the workforce, nurses have demonstrated less ability to influence legislative changes to health policy than other professions (Ellenbecker et al, ). Nurses do not have that much of ability to influence the legislative changes to the health policy unlike other professions (O'Rourke, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nursing educational institutions can include health policy as part of the curriculum. Research has shown that policy knowledge is associated with increased political participation (O'Rourke et al ). Although many educational programmes emphasize legislative policy and its process, developing political competencies is largely absent (Benton et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses’ contributions to policy development include identifying policy implementation problems and solutions, rational agenda setting, policy formulation, raising public awareness of healthcare issues and suggesting possible solutions or recommendations on policy review. However, evidence indicates that nurses (Kunaviktikul et al ) and nurse practitioners (O'Rourke et al ) have little recorded participation in policy development. This is largely due to lack of awareness and skill in policy development (Brokaw ), remaining silent (Schaeffer ), having few nurses in key positions (Varghese et al ), lack of time available to get involved (AbuAlRub & Foudeh ) and nurses lack confidence in their engagement ability in policy development (Ellenbecker et al ).…”
Section: Background and Significance Of Research Problemmentioning
confidence: 99%